2004
DOI: 10.1211/0022357022548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MX-68 on airway inflammation and hyperresponsiveness in mice and guinea-pigs

Abstract: MX-68 is a newly synthesized antifolate, which is a derivative of methotrexate (MTX). In this paper, the effect of MX-68 on allergic airway responses in mice and guinea-pigs was studied. In the first experiment, antigen-induced airway inflammation and airway hyperresponsiveness (AHR) to acetylcholine in mice were examined and compared with the effects of classical antifolate methotrexate and prednisolone. Mice were sensitized with ovalbumin as an antigen and challenged with ovalbumin inhalation three times. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…22) The guinea pig asthmatic model exhibits two phases, IAR over a few minutes and LAR during a few hours after antigen exposure. 23) Regarding guinea pig IAR and the LAR model, it is known that antihistamine suppresses IAR but not LAR, 24) anti-TXA 2 suppress IAR 25) and that anti-LT suppresses both IAR and LAR. 26) In addition, b2-agonists like salbutamol suppress only IAR but not LAR, indicating that IAR is mainly medi- ated by airway smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…22) The guinea pig asthmatic model exhibits two phases, IAR over a few minutes and LAR during a few hours after antigen exposure. 23) Regarding guinea pig IAR and the LAR model, it is known that antihistamine suppresses IAR but not LAR, 24) anti-TXA 2 suppress IAR 25) and that anti-LT suppresses both IAR and LAR. 26) In addition, b2-agonists like salbutamol suppress only IAR but not LAR, indicating that IAR is mainly medi- ated by airway smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, MESC did not affect body weight gains or spleen/ body weight ratios. In a previous study by Nagao et al (20), it was reported that corticosteroid-induced weight loss was the result of adverse reactions. In addition, the spleen mass reduction observed in the DEX group could have reflected general immune suppression, which is one of the major side effects of corticosteroids.…”
Section: Discussionmentioning
confidence: 97%
“…In a mouse asthmatic model, IAR is decreased by repeated antigen exposure [9], consistent with our findings. However, in a guinea pig asthmatic model, IAR and LAR were commonly provoked together after antigen challenge [18]. It is unclear why IAR disappeared or was diminished in some models of LAR.…”
Section: Discussionmentioning
confidence: 97%